Pengaruh Minyak Atsiri Asal Kulit Jeruk Manis Dan Besar Terhadap Perkembangan Tungau Panonychus Citri (Acarina: Tetranychidae) : The Effects Of Essential Oil Extracted From The Peel Of Sweet Orange And Pumello On The... - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2003)
Abstract: P. citri (Acarina: Tetranychidae) is one ofthe economically important citrus pests in Indonesia However, the association ofthis pestwith its host is notwell understood.. The objective of this research was to evaluate the effects of essential oil extracted fromf sweet orange and pumello fruit peels on the development of P. citri. The research was conducted in the laboratory ofIP2TPTlekung Malang, using a complete random design consisted of six treatments. Fifteen mites were used for each treatment. The treatments were concentrations 10, 20, 40, and 80 ppm ofessential oil. Parafin was used as a positive control because it was a diluting solutionfor the essential oil. The control received no application. The result showed that the main content of essential oil extracted from sweet orange and pumello was limonene. The essential oils prolonged the life cycle and reduced the fecundity of P. citri. The effects of essential oil extracted from pumello were found to be more pronounced than were from sweet orange. These differences might be due to the differences in the composition of the volatile compounds other than limonene.